Gull wing midforehead lift: when a poor man's forehead lift becomes the treatment of choice for brow ptosis - Huijing, Marijn A; van der Lei, Berend (Annals of plastic surgery, 2010)
In case of both medial and lateral brow ptosis in a balding candidate with a furrowed forehead, one may consider a midforehead lift, a technique that has not gained much popularity because of concerns regarding clearly visible scarring. We have applied this technique in a selected group of patients and wish to share our experience discussed among a review of the English-language literature. Our series of 10 male patients (average age, 56.9; operated in period between 2003 and 2006) were contacted, asked to return for a follow-up, and interviewed; all data were collected, including the excised amount of tissue and postoperative complications. Patient satisfaction was assessed (Likert scale) as well as the objective aesthetic result using the Strasser scoring system. Eyebrow position increased significantly (P < 0.035) after surgery, and remained stable over the follow-up period of 3 years. Postoperatively, the majority of the patients (7 of 10) was satisfied with the result and would repeat surgery based on their experience (average visual analog scale score, 7; range, 4-8). In all cases, functional complaints had decreased significantly. Although most patients reported to be somewhat bothered with the initial aesthetical aspect of the scar, only 1 of 10 patients was not satisfied with the overall aesthetic result. Four patients were graded as good, 3 patients as mediocre, and 1 patient as poor as based upon the Strasser grading system. These results demonstrate that there is a limited but definite indication for the gull wing midforehead lift in cases of generalized ptosis of the forehead in balding males with high and furrowed foreheads.